2006
DOI: 10.1099/mic.0.28881-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion to and viability on positively charged polymer surfaces

Abstract: Secondary and tertiary amino groups were introduced into polymer chains grafted onto a polyethylene flat-sheet membrane to evaluate the effects of surface properties on the adhesion and viability of a strain of the Gram-negative bacterium Escherichia coli and a strain of the Gram-positive bacterium Bacillus subtilis. The characterization of the surfaces containing amino groups, i.e. ethylamino (EA) and diethylamino (DEA) groups, revealed that the membrane potentials are proportional to amino-group densities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 45 publications
3
97
0
Order By: Relevance
“…A study of bacterial attachment to clays showed that most 2:1 clays enhanced respiration, while 1:1 clays had minimal effect (43). It has also been observed that positively charged surfaces can reduce cell viability (13,26,44,47). Unfortunately, given these disparate results, the prediction of how a specific surface may affect bacterial metabolic activity remains elusive.…”
mentioning
confidence: 99%
“…A study of bacterial attachment to clays showed that most 2:1 clays enhanced respiration, while 1:1 clays had minimal effect (43). It has also been observed that positively charged surfaces can reduce cell viability (13,26,44,47). Unfortunately, given these disparate results, the prediction of how a specific surface may affect bacterial metabolic activity remains elusive.…”
mentioning
confidence: 99%
“…The result of this treatment was due to increased amine groups on the anode surface which facilitates better attachment by the bacteria which are negatively charged (Silhavy et al 2010). Better attachment in turn influences better electron transfer (Terada et al 2006). Further, functionalization of dimethylaniline groups on carbon cloth anode was done by using the compound 4(N,N-dimethylamino)benzene diazonium tetrafluoroborate to increase the nitrogen groups present on the surface and this functionalization individually was also varied as well as compared with that by ammonia gas treatment (Saito et al 2011).…”
Section: Anode Performancementioning
confidence: 99%
“…Furthermore, they state that bacterial cell wall structures are likely to very much affect the viability [162] and this should be accounted for in future studies which are likely to investigate bacterial cell-substrate interactions. Whilst Terada and coworkers [161,162] showed that radiation grafting gave rise to an increase in bacterial adhesion, this is contrasted by Nava-Ortiz et al [164] who showed that Candida albicans adhesion can be reduced, preventing the formation of a biofilm on polyethylene (PE) and polypropylene (PP). It should be noted that Candida albicans is a fungus which, although forms a biofilm, has a very different adhesion and growth mechanism when compared to other forms of bacteria.…”
Section: Radiation Graftingmentioning
confidence: 99%
“…In addition, they carried out in vivo studies to AAm and HEMA grafted EPR, showing that CO 2 laser grafting can be employed to enhance the bioactivity of EPR [160]. Radiation grafting has been applied for the development of surfaces for the scientific study and control of bacterial adhesion and growth [34,[161][162][163][164][165][166]. The works of Terada and coworkers [161,162] showed how grafting diethlamine (DEA), ethylamino (EA) and sodium sulphite (SS) onto polymeric surfaces can manipulate bacterial adhesion and viability.…”
Section: Radiation Graftingmentioning
confidence: 99%